2015
DOI: 10.1002/chem.201503796
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocaloric Properties of Heterometallic 3d–Gd Complexes Based on the [Gd(oda)3]3− Metalloligand

Abstract: A series of heterometallic 3d-Gd(3+) complexes based on a lanthanide metalloligand, [M(H2 O)6 ][Gd(oda)3 ]⋅3 H2 O [M=Cr(3+) (1-Cr)] (H2 oda=2,2'-oxydiacetic acid), [M(H2 O)6 ][MGd(oda)3 ]2 ⋅3 H2 O [M=Mn(2+) (2-Mn), Fe(2+) (2-Fe) and Co(2+) (2-Co)], and [M3 Gd2 (oda)6 (H2 O)6 ]⋅12 H2 O [M=Ni(2+) (3-Ni), Cu(2+) (3-Cu), and Zn(2+) (3-Zn)], are reported. Magnetic and heat-capacity studies revealed a significant impact on the magnetocaloric effect depending on the anisotropy of the 3d transition metal ions, as conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Based on the above considerations, various 3d‐Ln III cluster‐based‐CPs, serving as molecular magnetic refrigerants, have been extensively synthesized and investigated (Tables and ),68–110,113 including Mn–Ln, Co–Ln, Ni–Ln, Cu–Ln, Cr–Ln, Fe–Ln, and Zn–Ln.…”
Section: Recent Advances In Coordination‐cluster‐based Molecular Magnmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above considerations, various 3d‐Ln III cluster‐based‐CPs, serving as molecular magnetic refrigerants, have been extensively synthesized and investigated (Tables and ),68–110,113 including Mn–Ln, Co–Ln, Ni–Ln, Cu–Ln, Cr–Ln, Fe–Ln, and Zn–Ln.…”
Section: Recent Advances In Coordination‐cluster‐based Molecular Magnmentioning
confidence: 99%
“…Very recently, through the self‐assembly of {Gd(oda) 3 } units with different 3d metal ions, Tong et al reported an ion‐pair compound, [Cr III (H 2 O) 6 ][Gd(oda) 3 ] · 3H 2 O ( 142 ), and a series of 3D frameworks, {[M II (H 2 O) 6 ][M II Gd(oda) 3 ] 2 · 6H 2 O} n (M=Mn II for 143a , Fe II for 143b , and Co II for 143c ) and {[ M3IIGd 2 (oda) 6 (H 2 O) 6 ] · 6H 2 O} n (M=Ni II for 144a , Cu II for 144b , and Zn II for 144c ) 28a,110. Magnetic and heat capacity measurements indicate a significant effect on the MCE, depending on the anisotropy of the 3d metal ions, as evidenced by a comparison of the experimental maximum values of –Δ S m between CPs 142 and 136c .…”
Section: Recent Advances In Coordination‐cluster‐based Molecular Magnmentioning
confidence: 99%
“…Polymeric 3d/4f complexes have also been isolated by such an in situ synthesis. [36][37][38][39][40][41][42][43][44][45] Nevertheless, there have been several reports of polymeric 3d/4f species obtained by the so called "metal complex as ligand" strategy, where a pre-isolated metal complex serves as a "metalloligand". [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] This strategy is based on ligands with usually N and O donor atoms on their inner shell and N or O atoms on their outer shell.…”
Section: Introductionmentioning
confidence: 99%
“…There has been an increasing interest in the synthesis and characterization of new 3d/4f complexes mainly due to their interesting magnetic properties which most often originate from the inherent uniaxial anisotropy of the 4f ions [1–9] . The combination of 3d and 4f metal ions may result in either discrete polynuclear metal complexes [10–35] exhibiting high spin ground states and in several occasions single‐molecule magnet behavior or in polymeric species [36–45] …”
Section: Introductionmentioning
confidence: 99%
“…They contain five atoms that are potential donors and have great potential in constructing metal complexes with intriguing architectures and new framework topologies [1][2][3]. For these reasons, they are commonly used for the synthesis of coordination polymers of a potential relevance for solid state technologies [4,5].…”
Section: Introductionmentioning
confidence: 99%